Chinese Ethnic Coffee Shop Adaptation in Riau through Inclusivity in Malay Society (KEMANUSIAAN The Asian Journal of Humanities, 2024)
This article focused on non-Muslim Chinese ethnic coffee shop entrepreneurs, aiming to discover and analyse forms of adaptation that have led to the survival of these coffee shops and their acceptance by the Malay-Muslim community. This qualitative research, utilising an ethnographic approach, is situated in Pekanbaru. Data was collected through observation and interviews with 11 predetermined informants, including entrepreneurs from second and third-generation Chinese families, Malay Riau cultural figures, historians, tourism advocates, coffee enthusiasts and customer informants. Documentary data in the form of autobiographies/biographies of the early founders of coffee shops. This study identified forms of adaptation, including the coffee shop managers’ identification with the community, continuity of family management adhering to halal and hygienic standards, prioritising honesty to gain community trust, forming partnerships and employing Muslim-background workers, and fostering communication, organisation, social engagement, and philanthropy. The adaptation of coffee shop entrepreneurs was expedited by the openness and acceptance of Muslim traders in Pekanbaru since the early 20th century. The presence of these coffee shops, deeply rooted in the social and cultural life of the Malay-Muslim community, manifests inclusivity. This encompasses accepting the halal aspect of the coffee shops’ offerings, managed by non-Muslim Chinese ethnic groups.